2018
DOI: 10.1016/j.ebiom.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Composition Drives Immune Activation in HIV-infected Individuals

Abstract: The inflammatory properties of the enteric microbiota of Human Immunodeficiency Virus (HIV)-infected individuals are of considerable interest because of strong evidence that bacterial translocation contributes to chronic immune activation and disease progression. Altered enteric microbiota composition occurs with HIV infection but whether altered microbiota composition or increased intestinal permeability alone drives peripheral immune activation is controversial. To comprehensively assess the inflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
111
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 63 publications
13
111
1
2
Order By: Relevance
“…This FOXP3+ association is concordant with prior work that shows an increase in regulatory T cells in response to stimulation with Bacteroides fragilis lysates (10). Prior work also shows an induction of CD4+HLA-DR+CD38+ T cells in response to stimulation with whole fecal bacterial communities (30). While we have not previously focused on HLA-DR+CD38cells, others suggest that HLA-DR+CD38-CD4+ T cells have a different functional profile than do HLA-DR+CD38+ cells in gut-associated lymphoid tissue in HIV (31).…”
Section: Case Study 3: Microbiome:immune Cell Relationships In Hivsupporting
confidence: 88%
See 1 more Smart Citation
“…This FOXP3+ association is concordant with prior work that shows an increase in regulatory T cells in response to stimulation with Bacteroides fragilis lysates (10). Prior work also shows an induction of CD4+HLA-DR+CD38+ T cells in response to stimulation with whole fecal bacterial communities (30). While we have not previously focused on HLA-DR+CD38cells, others suggest that HLA-DR+CD38-CD4+ T cells have a different functional profile than do HLA-DR+CD38+ cells in gut-associated lymphoid tissue in HIV (31).…”
Section: Case Study 3: Microbiome:immune Cell Relationships In Hivsupporting
confidence: 88%
“…Previously, Regner et al reported on relationships between the gut microbiome and cytokines produced by mitogen-stimulated intraepithelial lymphocytes (IEL) in patients with spondyloarthritis (SpA), Crohn's disease (CD), ulcerative colitis (UC), and healthy controls (HC) (30). Among other results, Regner identified elevated levels of TNFα in patients with SpA and CD.…”
Section: Case Study 2: Microbiome:immune Cell Relationships In Inflammentioning
confidence: 99%
“…In a separate study, we have used in vitro stimulations with collections of whole intact bacterial cells isolated from feces, and found that MSM microbiomes induced more pro-inflammatory innate immune activation compared to non-MSM controls (2). Several OTUs more abundant in Prevotella-rich MSM compared to Prevotella-rich non-MSM, but not any OTUs in the Prevotella genus, correlated strongly with high CD4+ and CD8+ T cell activation in these in vitro stimulations (2). We have also previously used in vitro stimulation assays to show that one of these MSM and immune-activation correlated bacteria, Holdamenella biformis ATCC 27806 (formally Eubacterium biforme ) but not P. copri DSM-18205 is far more pro-inflammatory than other gut commensals tested, inducing high TNF-α to IL-10 ratio in peripheral blood mononuclear cell (PBMC) stimulations (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, the gut microbiome may hold the key for preventing disease transmission and progression and for improving the quality of life for the 1.2 million Americans and 36.7 million individuals worldwide with chronic HIV infection for several reasons (1). First, the gut microbiota can induce T cell activation (2) and since HIV preferentially infects activated T cells, microbiome composition at mucosal sites, specifically in the rectum/anus, may influence disease transmission in men who have sex with men (MSM) (3–5). Second, increased peripheral immune activation driven by translocation of gut bacterial components has been linked to HIV disease progression in both untreated and treated infection (6), and the high peripheral immune activation may be influenced by gut microbiota with more pro-inflammatory components (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation